Reported Changes in Dietary Habits During the COVID-19 Lockdown in the Danish Population: The Danish COVIDiet Study - Giacalone, Davide; Frøst, Michael Bom; Rodríguez-Pérez, Celia (Frontiers in Nutrition, 2020)
This paper focuses on the effect of the COVID-19 lockdown on the dietary habits of adult Danes. Two aspects were specifically considered: 1) reported changes in intake of specific food categories and 2) effect on healthy eating, operationalized as adherence to the Mediterranean diet (MEDAS score). Respondents (N= 2462) completed a 44-items self-administered online survey designed for the assessment of their socio-demographic characteristics, general food habits, and consumption frequency of selected foods (mainly related with the MedDiet) during the lockdown. The data indicated that the lockdown has affected dietary habits of adult Danes to a relatively limited degree. The most important findings were that a substantial proportion of respondents (≥28%) reported eating more, snacking more, exercising less, and gaining weight during the lockdown. Results could be linked to the amount of time spent at home (e.g., a higher cooking frequency) a higher degree of emotional eating during the lockdown (e.g., a higher consumption of pastries and alcohol). Women were generally affected to a higher degree than men. Additionally, dietary changes during the lockdown to a certain degree reflected pre-existing (un)healthy eating habits, as positive health outcomes were observed in respondents with a high MEDAS score and negative outcomes (e.g., weight gain and higher intakes of pastries and carbonated beverages) were associated with respondents with a low MEDAS score. These changes, if sustained long-term, are potentially concerning from a public health perspective, especially given that more than half of the respondents were characterized by a low adherence to the MedDiet.